Findbuch der Bestände Abt. 18 und Abt. 19: Generalsuperintendent für Schleswig und Generalsuperintendent für Holstein - Rathjen, Jörg (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2016)
The Generalsuperintendent" supervised the church, school and poor people. He had a seat and a voice in the "Oberkonsistorium" (Upper Consistory) as well as in the "Landoberkonsistorium " (Country Upper Consistory) which was responsible for the noble as well as the monastic areas. Since 1636 the name "Generalsuperintendent" was in use. The royal and the Gottorf general superintendents were each responsible for the shares of their sovereigns in both dukedoms, Schleswig and Holstein. The unification of the royal and Gottorf districts in Schleswig in 1720 led to the fact that the supervision of the royal "Generalsuperintendent" extended once and for all over the entire duchy of Schleswig. From 1784 onwards, the duchy of Holstein was united under the royal "Generalsuperintendent". In 1834, the office was divided into one area of responsibility for Schleswig and one for Holstein. With the introduction of the Schleswig-Holstein church constitution in 1922, the office "Generalsuperintendent" was abolished and replaced by the regional bishop. This find book is based on a re-listing of the holdings of the archives of the General Superintendentury in 2011: denotation and duration of all archive records have been reviewed. Extensive and difficult to understand file denotations have been replaced by shorter and more modern ones. Older terms have been retained as long as they represent common search terms. Extensive files divided and new numbers created. In addition, the archive records were given new numbering. A concordance at the end of the find book shows under which new signatures the old numbers can be found. A register of places, subjects and persons forms the conclusion of this find book. As a rule, classification terms are not included."